BIOELECTRIC POTENTIALS IN VALONIA : II. EFFECTS OF ARTIFICIAL SEA WATERS CONTAINING LiCl, CsCl, RbCl, OR NH(4)Cl - Damon, E. B. (The Rockefeller University Press, 1939)
In their influence on the P.D. across the protoplasm of Valonia macrophysa, Kütz., Li(+) and Cs(+) resemble Na(+), while Rb(+) and NH(4) (+) resemble K(+). The apparent mobilities of the ions in the external surface layer of Valonia protoplasm increase in the order: Cs(+), Na(+), Li(+) < Cl(-) < Rb(+) < K(+) < NH(4) (+).